THE DEVELOPMENT OF AN INNOVATIVE SET OF APPLIED FOLK SONGS BASED ON FOOD WISDOM FROM SUGAR PALM, SANKHABURI DISTRICT, CHAINAT PROVINCE FOR INTEGRATED LEARNING MANAGEMENT IN FUNDAMENTAL EDUCATION CLASSROOMS - Wiwanthamongkon, Karanphon; Suphannyot, Buaphan; Wiwanthamongkhon, Phatsakon; Pinkaeo, Chuleekorn; Pinkaeo, Surapong; Netniyom, Anannya; Kitchanulak, Rewatta (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2026)
This research aimed to: (1) study the local identity of palm (tan) wisdom in Sankhaburi District and propose approaches for developing creative song innovations, (2) develop an applied folk song innovation using palm-based food wisdom, (3) design integrated learning management incorporating the innovation, and (4) evaluate the outcomes of implementing the innovation in classroom learning. The study employed a Research and Development (R&D) methodology. The participants were 25 fundamental education teachers who voluntarily participated in the study from Sankhaburi District, Chainat Province. Research instruments included interviews, expert evaluation forms, learning management assessment forms, and reflective journals. Data were analyzed using percentage, mean, standard deviation, and content analysis. The results revealed that: (1) the palm (tan) wisdom of Huai Krot Subdistrict represents a distinctive cultural identity of the Sankhaburi community and should be further developed and integrated into education to preserve and transmit local wisdom sustainably, (2) the developed innovation, an applied folk song titled “Plai Jowak Tan Sankhaburi” composed in the traditional Choi rhythm, was rated by experts at the highest level for creativity, cultural integration, and educational value, (3) the instructional design integrating this innovation demonstrated high quality in terms of content structure, learning activities, and teacher competency, and (4) classroom implementation achieved highly effective results. Teachers were able to extend and adapt the innovation to strengthen local learning, while students showed creativity in project-based activities using palm wisdom, enhancing their vocational and life skills. Overall, the study emphasizes that integrating local wisdom through innovative folk song-based learning promotes cultural preservation, creativity, and sustainable education that connects schools, teachers, and communities.